INFLUENCE OF URBANIZATION ON THE LEVEL OF PHYSICAL FITNESS AND GENERAL MORBIDITY OF FIRST-YEAR FEMALE STUDENTS - Strelnikova, I.V.; Kiseleva, N.V.; Maltsev, D.N.; Dudkina, Y.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was a comparative assessment of physical fitness and the level of general morbidity of female students who lived before entering the university in territories of varying degrees of urbanization. Methods and structure of the study. 401 first-year students of VyatSU, Kirov, took part in the scientific work. The subjects were divided into three groups, according to their places of residence before entering the university. The first group consisted of girls from the city of Kirov (“a large city”, the population is more than 250,000–500,000), the second group included students from providing “small towns” of the Kirov region (12,000–20,000) and the third group united first-year students from rural locality (<3,000 people). Results and conclusions. The level of urbanization affects the degree of general morbidity and physical fitness of 17-18-year-old female students living in a large city before entering a university. The group of first-year girls in Kirov has a low level of the number of the main medical group in physical culture and a high degree of morbidity of the respiratory organs. Reliably significant differences were also revealed in relation to girls from rural settlements of dependence in tests on strength fitness and endurance.